Source Term Identification with Discontinuous Dual Reciprocity Approximation and Quasi-Newton Method from Boundary Observations (Journal of Computational Mathematics, 2021)
This paper deals with discontinuous dual reciprocity boundary element method forsolving an inverse source problem. The aim of this work is to determine the source term inelliptic equations for nonhomogenous anisotropic media, where some additional boundarymeasurements are required. An equivalent formulation to the primary inverse problem isestablished based on the minimization of a functional cost, where a regularization term isemployed to eliminate the oscillations of the noisy data. Moreover, an efficient algorithmis presented and tested for some numerical examples.
Keywords: Boundary element method; Inverse source problem; Quasi-Newton methods.